FtsK Is a DNA motor protein that activates chromosome dimer resolution by switching the catalytic state of the XerC and XerD recombinases. - Aussel, L; Barre, F; Aroyo, M; Stasiak, A; Stasiak, A; Sherratt, D (2002)
FtsK acts at the bacterial division septum to couple chromosome segregation with cell division. We demonstrate that a truncated FtsK derivative, FtsK(50C), uses ATP hydrolysis to translocate along duplex DNA as a multimer in vitro, consistent with FtsK having an in vivo role in pumping DNA through the closing division septum. FtsK(50C) also promotes a complete Xer recombination reaction between dif sites by switching the state of activity of the XerCD recombinases so that XerD makes the first pair of strand exchanges to form Holliday junctions that are then resolved by XerC. The reaction between directly repeated dif sites in circular DNA leads to the formation of uncatenated circles and is equivalent to the formation of chromosome monomers from dimers.